2014
DOI: 10.4103/0019-5278.134946
|View full text |Cite
|
Sign up to set email alerts
|

A study on morbidity among automobile service and repair workers in an urban area of South India

Abstract: Introduction:Service sector in Indian industrial growth has obtained significant numbers. Automobile service industry is one of the largest in the world with a majority of the workers in unorganized sector of the industry. This study was carried out among auto service industry workers in Vellore urban area to assess possible occupation related morbidity.Materials and Methods:A cross-sectional observation study was carried out among 106 automobile repair shop workers.Results:Half (47%) suffered work related str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
9
2
Order By: Relevance
“…Perceived exposure to dust was 76% compared to 40% in this study. Overall perception of exposure to chemicals and hazardous agents in this study ranged from 8.6%-62%, with highest perceived exposure reported for carbon monoxide, whereas Philip et al reported perceived exposure ranging from 50-90.6%, much higher than findings from this study 12 . The findings indicate that despite being a smallscale workplace, health and safety conditions had not been disregarded in this automotive workplace in UAE.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Perceived exposure to dust was 76% compared to 40% in this study. Overall perception of exposure to chemicals and hazardous agents in this study ranged from 8.6%-62%, with highest perceived exposure reported for carbon monoxide, whereas Philip et al reported perceived exposure ranging from 50-90.6%, much higher than findings from this study 12 . The findings indicate that despite being a smallscale workplace, health and safety conditions had not been disregarded in this automotive workplace in UAE.…”
Section: Discussioncontrasting
confidence: 81%
“…As the shift system was not applied in this private company, this finding merits further exploration. Skin rashes and breathing issues were mentioned under acute health issues, as have been observed in other studies 12 ; however, the percentage of complaints of rash was considerably lower than seen in a study on automotive repair shops in Egypt, but comparable to a study done in South India. On the other hand, breathing problems were reportedly higher in the study conducted in south India and Ghana 9,22 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other studies in Nigeria and India even revealed that no respondents received any form of training on workplace safety. [ 1 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The automobile service industry has a large group of workers with many being in the unorganized sector. [ 1 ] They are involved in numerous activities which expose them to many physical, biological, and chemical agents that can be hazardous to their health. [ 2 ] These workers are also prone to workplace accidents and injuries, many of which are preventable.…”
Section: Introductionmentioning
confidence: 99%